A randomized clinical trial of nasogastric tube insertion in intubated patient: comparison between finger method and reverse Sellick maneuver (Medical Journal of Indonesia, 2019)
BACKGROUND Finger method is a new simple technique of nasogastric tube (NGT) insertion for intubated patients which only requires the practitioner's own fingers. This study was aimed to compare the feasibility of finger method and the standard reverse Sellick maneuver in NGT insertion for intubated patients. METHODS This was a single-blinded, randomized clinical trial that included 210 patients aged 18–65 years old who were intubated under general anesthesia and needed NGT insertion. Initially, subjects were randomly allocated by the third party into two groups: subjects who had NGT insertion with finger method and those with reverse Sellick maneuver. Success rate of NGT insertion at the first attempt, duration of the procedure, and complication rate of blood spots were all recorded. Chi-square test and Mann–Whitney analysis were used to analyze the data. RESULTS Success rate of NGT insertion at the first attempt in finger method group was higher in comparison with reverse Sellick maneuver group (81.6% versus 60%, respectively, p = 0.002). Likewise, the median of NGT insertion duration was longer in finger group compared to reverse Sellick maneuver group (13 sec versus 12 sec, respectively, p < 0.001) but it was not clinically significant. Moreover, the complication rate of blood spots found during the procedure was lower in subjects with finger method than with reverse Sellick maneuver (10.7% versus 28%, respectively, p = 0.003). CONCLUSIONS Using finger method was more feasible than reverse Sellick maneuvers in NGT insertion.